Occurrence of Parasitoid, Leiophron Sp. (Hymenoptera: Braconidae), on Adults of Helopeltis antonii Signoret in Cashew - Bhat, P S; Srikumar, K K (Journal of Horticultural Sciences, 2014)
Helopeltis antonii is a major pest of cashew, cocoa, neem, guava and pepper in the old world tropics. Survey for parasites identified a parasitoid, Leiophron sp. (Hymenoptera: Braconidae), on adults of H. antonii. The parasitism was low (1.3%), of which 59.4% was observed during the month of June. Size of the parasitoid larvae was 3.66 ± 0.11mm in length, and 1.31±0.03mm in breadth. Pre-pupation period was 1.75±0.22 days. Copulation was observed between parasitized H. antonii males and females indicating, that, mating was not affected by parasitism. Parasitoid activity showed significant positive correlation (r = 0.62; P = 0.05) with rainfall. Parasitism provided by this parasitoid certainly warrants further investigation on biological control of this economically important pest.